The activities of the Commission for combating desertion of labour of the Omsk province in 1920–1921 - T. V. Glazunova (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study of organization and activities of the Omsk provincial Committee for the fight against labor desertion (Omgubkomtruddezertir). Based on the analysis of the legislative base of the 1919–1921’s and the office documentation of the Omgubkomtruddezertir (reports, summaries, reports), its composition, main functions and mechanisms for combating labor desertion are studied. The difficulties and specifics of the organization of the fight against labor desertion in the Omsk province are revealed. The author comes to the conclusion that despite the difficulties encountered, the lack of employees, insufficient work experience, Omgubkomtruddezertir, in general, successfully solved the tasks assigned to it